Germline BRCA mutation does not prevent response to taxane‐based therapy for the treatment of castration‐resistant prostate cancer - Gallagher, David J.; Cronin, Angel M.; Milowsky, Matthew I.; Morris, Michael J.; Bhatia, Jasmine; Scardino, Peter T.; Eastham, James A.; Offit, Kenneth; Robson, Mark E. (BJU international, 2012)
Study Type – Prognosis (case series) Level of Evidence 4 What’s known on the subject? and What does the study add? In the preclinical setting BRCA mutations appear to modulate response to chemotherapy, increasing sensitivity to platinums and increasing resistance to taxanes. Clinical data supports a greater platinum sensitivity among BRCA mutation carriers. This study suggests that BRCA mutation carriers may also respond to taxanes. OBJECTIVE • To investigate the relationship between BRCA mutation status and response to taxane‐based chemotherapy, since BRCA mutation carriers with prostate cancer appear to have worse survival than non‐carriers and docetaxel improves survival in patients with castration‐resistant prostate cancer. PATIENTS AND METHODS • We determined BRCA mutation prevalence in 158 Ashkenazi Jewish (AJ) men with castration‐resistant prostate cancer. Clinical data were collected as part of an institutional prostate cancer research database and through additional medical record review. • Clinical records and DNA samples were linked through a unique identifier, anonymizing the samples before genetic testing for the AJ BRCA1/2 founder mutations. • Response to taxane‐based therapy was defined by the prostate‐specific antigen nadir within 12 weeks of therapy. RESULTS • In all, 88 men received taxane‐based treatment, seven of whom were BRCA carriers (three BRCA1, four BRCA2; 8%). Initial response to taxane was available for all seven BRCA carriers and for 69 non‐carriers. • Overall, 71% (54/76) of patients responded to treatment, with no significant difference between carriers (57%) and non‐carriers (72%) (absolute difference 15%; 95% confidence interval –23% to 53%; P= 0.4). • Among patients with an initial response, the median change in prostate‐specific antigen was similar for BRCA carriers (−63%, interquartile range −71% to −57%) and non‐carriers (−60%, interquartile range −78% to −35%) (P= 0.6). • At last follow‐up, all seven BRCA carriers and 49 non‐carriers had died from prostate cancer. One BRCA2 carrier treated with docetaxel plus platinum survived 37 months. CONCLUSION • In this small, hypothesis‐generating study approximately half of BRCA carriers had a prostate‐specific antigen response to taxane‐based chemotherapy, suggesting that it is an active therapy in these individuals.